IPv6 based SD-WAN deployment - Wei WANG (Dianxin kexue)
The development background of SD-WAN and the current SD-WAN scheme based on IPv4 was introduced,the scheme of applying IPv6 to SD-WAN scenario was put forward,the changes that need to be made at the existing underlay and overlay levels to realize the SD-WAN scheme based on IPv6 were analysed,and the feasibility of using IPv6 technology to realize SD-WAN was discussed.